Bilingualism in a multilingual society psycho-social and pedagogical implications - Ajit K. Mohanty (My University, 1994)
It is a report of the research supported by the Institute and it deals with the important subject of bilingualism in its psychological and pedagogical dimensions in the context. This study is a contribution to research on bilingualism in the Indian context and is relevant for language education, particularly for linguistic minorities.
Keywords: English